2016
DOI: 10.3126/stcj.v2i1.14801
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Evaluation of Bottled Water Commercially Available in Eastern Nepal

Abstract: The demand for bottled water is high in these days and it has been a growing concern about the microbiological quality of such processed water. The objective of this study was to assess the heterotrophic contamination and total coliform. This cross-sectional study was carried out in randomly selected 24 different commercial brands of bottled water available in the commercial market of the eastern region of Nepal. Total coliform and heterotrophic bacteria were enumerated by the membrane filtration and spread pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Unlike our study, as reported in the previous studies done in Nepal, only 10% to 80% of the bottled water samples were free from microbial (Timilshina, et al, 2012;Rai, et al, 2015;Pant, et al, 2016;Maharjan, et al, 2018). In studies done in India, the acceptability of bottled water samples based on the bacteriological parameter ranged from 55% (Gangil, et al, 2013) , 60% (Jeena, et al, 2006;Jain, et al, 2012), 62.5% (Joseph, et al, 2018), 66.7% (Venkatesan, et al, 2014), 73.33% (Bency, et al, 2010), 83% (Sharma & Kaur, 2015) to even 100% (Singla, et al, 2014).…”
Section: Discussioncontrasting
confidence: 97%
“…Unlike our study, as reported in the previous studies done in Nepal, only 10% to 80% of the bottled water samples were free from microbial (Timilshina, et al, 2012;Rai, et al, 2015;Pant, et al, 2016;Maharjan, et al, 2018). In studies done in India, the acceptability of bottled water samples based on the bacteriological parameter ranged from 55% (Gangil, et al, 2013) , 60% (Jeena, et al, 2006;Jain, et al, 2012), 62.5% (Joseph, et al, 2018), 66.7% (Venkatesan, et al, 2014), 73.33% (Bency, et al, 2010), 83% (Sharma & Kaur, 2015) to even 100% (Singla, et al, 2014).…”
Section: Discussioncontrasting
confidence: 97%
“…The studies carried out in different parts of Nepal also depicted a similar type of picture as was found in this study. [20][21][22] Even though safe and clean drinking water has been categorized as basic human rights by the United Nation. The availability of safe drinking water, not least in developing countries, is still a distant reality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Sudarshana et al (2019), 84.5% of the samples from the Kathmandu municipality exceeded both NDWQS and WHO standards for total coliforms. A study by Rai et al (2015) reported that most of the bottled drinking water in eastern Nepal exceeded the WHO guidelines for E. coli and total coliforms. Koju et al (2014) found that groundwater samples from Kathmandu, Nepal, had higher levels of total coliforms than the WHO standard.…”
Section: Resultsmentioning
confidence: 99%